Communication interventions to promote the public's awareness of antibiotics: a systematic review - Valerie R. Burstein; Renee P. Trajano; Richard L. Kravitz; Robert A. Bell; Darshan Vora; Larissa S. May (BMC, 2019)
Abstract Background Inappropriate antibiotic use is implicated in antibiotic resistance and resultant morbidity and mortality. Overuse is particularly prevalent for outpatient respiratory infections, and perceived patient expectations likely contribute. Thus, various educational programs have been implemented to educate the public. Methods We systematically identified public-directed interventions to promote antibiotic awareness in the United States. PubMed, Google Scholar, Embase, CINAHL, and Scopus were queried for articles published from January 1996 through January 2016. Two investigators independently assessed titles and abstracts of retrieved articles for subsequent full-text review. References of selected articles and three review articles were likewise screened for inclusion. Identified educational interventions were coded for target audience, content, distribution site, communication method, and major outcomes. Results Our search yielded 1,106 articles; 34 met inclusion criteria. Due to overlap in interventions studied, 29 distinct educational interventions were identified. Messages were primarily delivered in outpatient clinics (N = 24, 83%) and community sites (N = 12, 41%). The majority included clinician education. Antibiotic prescription rates were assessed for 22 interventions (76%). Patient knowledge, attitudes, and beliefs (KAB) were assessed for 10 interventions (34%). Similar rates of success between antibiotic prescription rates and patient KAB were reported (73 and 70%, respectively). Patient interventions that did not include clinician education were successful to increase KAB but were not shown to decrease antibiotic prescribing. Three interventions targeted reductions in Streptococcus pneumoniae resistance; none were successful. Conclusions Messaging programs varied in their designs, and many were multifaceted in their approach. These interventions can change patient perspectives regarding antibiotic use, though it is unclear if clinician education is also necessary to reduce antibiotic prescribing. Further investigations are needed to determine the relative influence of interventions focusing on patients and physicians and to determine whether these changes can influence rates of antibiotic resistance long-term.